KAEMPFEROL, A FLAVONOID COMPOUND FROM GYNURA MEDICA INDUCED APOPTOSIS AND GROWTH INHIBITION IN MCF-7 BREAST CANCER CELL - yi, xiaofang; tan, chao; Zuo, Jiangcheng; Xian, Sheng; Luo, Chunhua; Chen, Sai; Yu, Liangfang; Luo, Yucheng (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Kaempferol, a natural flavonoid, has been shown to induce cancer cell apoptosis and cell growth inhibition in several tumors. Previously we have conducted a full investigation on the chemical constituents of Gynura medica, kaempferol and its glycosides are the major constituents of G. medica. Here we investigated the growth inhibition and apoptosis induction effect of kaempferol extracted from G. medica. Materials and Methods: The inhibition effects of kaempferol were evaluated by MTS assay and soft agar colony formation assay. Fluorescence staining and western blotting were be used to study the apoptosis. The structure was identified by 1H- NMR), 13C-NMR and ESI-MS analyses. Results: Our results showed that kaempferol’s inhibition of MCF-7 breast cancer cell growth may through inducing apoptosis and downregulation of Bcl2 expression. Conclusion: Kaempferol is a promising cancer preventive and therapeutic agent for breast cancer.